ElectroGes - a household IoT energy management system - Bento, Mariana (2019)
Domestic appliances plugged to the electrical mains power may, at some point, exceed the maximum contracted power supplied from the electrical company. To avoid a power cut-off on these cases, an energy management system is needed so that some appliances are automatically switched off before others are switched on. In order to do this, appliances have to be described in a privileged structure so that power is always available for some of them while other share leftovers. ElecroGes is a system that provides the house owner with a means to define the priorities of the connected appliances and manage them in an autonomous way; a working implementation is provided.